Analisis Pengendalian Internal Piutang Usaha Dalam Meminimalisir Piutang Tidak Tertagih - Agustina Maya; Kusuma Dewi (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
Credit sales are carried out by companies to attract many customers, so that the sales volume can increase compared to sales in cash. However, credit sales have several risks including uncollectible receivables. Hence, internal control of receivables is very important as receivables, in the future, must be recorded in cash flow. If there are customers who are overdue in payments or fail to settle their debts due to various reasons, the company’s operational activities will be disrupted. The purpose of this study is to determine the internal control of trade receivables in minimizing uncollectible receivables in a company. PT Bostinco is a manufacturing company that produces safes, filling cabinets, roll-o-pack sliding cabinets, fire doors, etc. In its regular sales practice, the company uses a credit sales system, preceded by down payment requirements based on the agreement between the seller and the customers. As credit sales made by the company will cause trade receivables, internal control is carried out to minimize the risk of uncollectible receivables. The results of the study show that internal control of accounts receivable in minimizing uncollectible receivables runs poorly due to the findings of the original Delivery Order files that are still discharged. Moreover, the company has some VAT debt arrears which prevents it from getting the tax invoice number. Unfortunately, there is no penalty agreement for late payment despite of quite large amount of receivables. Keywords: Internal Control of Accounts Receivable and Minimize Uncollectible Receivables